Pesan Akhlak dalam Program ”Jejak Islam” TVRI Sumatera Utara: Analisis Semiotika - Agustina, Dayana; Rubino (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Examining the "Jejak Islam" show on North Sumatra TVRI's YouTube channel for its moral message is the purpose of this study. This study focuses on the "Jejak Islam" segment of "Penerang Hati" on TVRI North Sumatra. A qualitative methodology based on semiotic analysis was applied in this investigation. Following Roland Barthes's theory of denotation, connotation, and myth, the research design provides a detailed description of the signs utilized in the "Jejak Islam" program and how these signals generate meaning. Thanks to their genuine desire to teach and practice the braille Quran, the moral lessons delivered in the "Jejak Islam" program's episode of "Penerang Hati" through Roland Barthes' semiotic analysis comprise of morality towards God, according to the research results. Social norms pertaining to other people, including deference to authority figures (such as professors), friendship, politeness, and parental respect.